The Concept of Bughat as a Political Crime in Islam - Chifa Azyana Adly meknesya; Nia Amelia Suhada Dalimunthe; Siti Kholizah; M. Abdillah; Rahman Al Fauzi Siregar (ISNU Nine-Star Multidisciplinary Journal, 2026)
This paper examines the concept of bughat as a form of political crime within Islamic law and its relevance to contemporary governance. The study is motivated by the enduring concern of Islamic jurisprudence for political stability, public security, and communal unity, particularly in responding to acts of rebellion against legitimate authority. Employing a normative legal research method, the study analyzes classical fiqh literature, Qur’anic verses, Prophetic traditions, and contemporary Islamic legal scholarship. The research stages include doctrinal analysis, contextual interpretation, and comparison between classical and modern perspectives. The findings demonstrate that bughat is not limited to armed rebellion but encompasses organized actions aimed at undermining legitimate authority and social order. The discussion highlights the legal, social, and political implications of bughat, emphasizing proportional enforcement, restorative justice, and the protection of public welfare (maṣlaḥah). Ultimately, the study concludes that the concept of bughat remains relevant as an ethical–juridical framework for maintaining political stability, preventing radicalism, and supporting just and democratic governance in modern contexts.